Sowing in Plastic Contaminated Soils: How (Micro)plastics Impact Seed Germination and Growth of White Mustard (Sinapis alba L.) - Špela Železnikar; Nina Kacjan Maršić; Marina Pintar (Applied Sciences, 2025)
Microplastic (MP) particles are ubiquitous in the environment and pose a growing threat to ecosystem stability. As concern over their ecological impact increases, biotests and ecotoxicological approaches using plant species have become valuable tools for research. This study aimed to evaluate the effects of varying concentrations of low-density polyethylene (LDPE) MP on seed germination, root development, and shoot growth of white mustard (Sinapis alba L.) under controlled laboratory and pot experiment conditions. For the seven-day laboratory experiment, concentrations of 0.01% and 1% w/w were used, whereas concentrations of 1% and 5% w/w were applied in the ten-day pot experiment. Results indicated no statistically significant effects of LDPE MP on germination rate or germination speed index (GSI) in either setting. However, shoot length data suggest that the 5% LDPE treatment may have a slight stimulatory effect compared to the control, though this trend was marginally significant. These findings highlight the complex and context-dependent nature of MP–plant interactions. Further research is needed to better understand the mechanisms driving these responses and to support the development of mitigation strategies for MP contamination in terrestrial ecosystems.